2021
DOI: 10.1007/s40259-021-00467-w
|View full text |Cite
|
Sign up to set email alerts
|

Biologics and Targeted Synthetic Drugs Can Induce Immune-Mediated Glomerular Disorders in Patients with Rheumatic Diseases: An Updated Systematic Literature Review

Abstract: Objective Our objective was to update the understanding of the development of paradoxical immune-mediated glomerular disorders (IGDs) in patients with rheumatic diseases treated with biologics and targeted synthetic drugs (ts-drugs). Methods A systematic literature review was performed by searching PubMed for articles published between 1 January 2014 and 1 January 2020 reporting on the development of IGD in adult patients with rheumatoid arthritis, psoriatic arthritis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It has been suggested that BAIRD might better fit an acronym for "Biologics Associated Immune-mediated Renal Disorders" which would be a more inclusive term (Piga's original paper only designated the acronym as "AIRD due to Biologics" and later authors added the "B" so the acronym is not yet established in stone). 4,6,11,38 This latter designation would then more closely fit with animal toxicity findings related to immunomodulatory therapies, where interstitial inflammation in the kidney has been identified with some of these new-generation alternative classes of medicine affecting STING and interferon pathways. 38 At present, these nonclinical immunomodulatory toxicities may only represent BAIRD-like lesions since BAIRD has not been accepted as a classification scheme in the nonclinical toxicology community.…”
Section: Car-t Therapiesmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that BAIRD might better fit an acronym for "Biologics Associated Immune-mediated Renal Disorders" which would be a more inclusive term (Piga's original paper only designated the acronym as "AIRD due to Biologics" and later authors added the "B" so the acronym is not yet established in stone). 4,6,11,38 This latter designation would then more closely fit with animal toxicity findings related to immunomodulatory therapies, where interstitial inflammation in the kidney has been identified with some of these new-generation alternative classes of medicine affecting STING and interferon pathways. 38 At present, these nonclinical immunomodulatory toxicities may only represent BAIRD-like lesions since BAIRD has not been accepted as a classification scheme in the nonclinical toxicology community.…”
Section: Car-t Therapiesmentioning
confidence: 99%
“…7-10 BAIRD lesions in humans that are associated with vasculitis often do not involve ADA, and may lack immune complex formation at the site of injury. 6,11 Lupus-like glomerular syndromes are extremely rare as a drug- or chemical-related toxicity in animals, as are “isolated autoimmune renal disorders.” 10 Therefore, none of the three forms of classification for BAIRD have specifically been applicable in nonclinical DIKI. Hence, BAIRD has been considered a clinical syndrome, and one that has not been utilized in the veterinary or nonclinical toxicologic pathology literature.…”
Section: Biotherapeuticsmentioning
confidence: 99%
See 3 more Smart Citations